2023
DOI: 10.1111/jan.15606
|View full text |Cite
|
Sign up to set email alerts
|

Irregular migrants' experiences of health disparities while living in informal settlements during the COVID‐19 pandemic

Abstract: Aims:The objective of this study was to describe and understand irregular migrants' (IMs') experiences of health disparities while living in informal settlements (ISs) during the COVID-19 pandemic.Design: Qualitative descriptive study. Methods: Thirty-four IMs originating from different African countries living in ISs took part in this study. Data were collected between January and March 2022 through three focus groups and 17 in-depth interviews. Thematic analysis was used to analyse qualitative data with ATLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In this study, the population reported a mean age of 33.29 years (SD: 9.11), 55.88% were men and 44.12% were women, with a mean length of residency in Spain of 5.09 years, and 35.29% of them did not work while 64.71% of them worked in greenhouses. [43] In this case, 2 similar realities coexist in southern Spain (from east to west). Another point to note was that the participants who reported their willingness to stay in Spain presented a higher mean score compared to those who wished to return to their country of origin (14 vs 12, respectively).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In this study, the population reported a mean age of 33.29 years (SD: 9.11), 55.88% were men and 44.12% were women, with a mean length of residency in Spain of 5.09 years, and 35.29% of them did not work while 64.71% of them worked in greenhouses. [43] In this case, 2 similar realities coexist in southern Spain (from east to west). Another point to note was that the participants who reported their willingness to stay in Spain presented a higher mean score compared to those who wished to return to their country of origin (14 vs 12, respectively).…”
Section: Discussionmentioning
confidence: 71%
“…In this study, the population reported a mean age of 33.29 years (SD: 9.11), 55.88% were men and 44.12% were women, with a mean length of residency in Spain of 5.09 years, and 35.29% of them did not work while 64.71% of them worked in greenhouses. [ 43 ] In this case, 2 similar realities coexist in southern Spain (from east to west).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…IMs lacked sufficient resources to be able to mitigate the consequences of the pandemic (18,19). Their legal status was an obstacle to accessing regularized employment or state benefits (20), thus increasing their exposure to the virus (21,22). They also had poor living conditions (23), which made it impossible to comply with virus prevention measures (24).…”
Section: Introductionmentioning
confidence: 99%